1994
DOI: 10.1073/pnas.91.2.674
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of differentiated, nontransformed hepatocyte cell lines derived from mice transgenic for transforming growth factor alpha.

Abstract: Hepatocytes are extensively used in studies of gene regulation but cannot be maintained in long-term culture as replicating, differentiated cells while remaining nontumorigenic. We have derived two hepatocyte lines from livers of transgenic mice overexpressing transforming growth factor a, a potent hepatocyte mitogen, which overcome these limitations. The transgenic hepatocytes were maintained for .2 months in serum-supplemented primary culture and gave rise to cell lines, of which two (AML12 and AML14) have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
202
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(209 citation statements)
references
References 24 publications
3
202
0
2
Order By: Relevance
“…To test this hypothesis we used mouse AML12 cells, a normal cell line that exhibits typical hepatocyte features, such as peroxisomes and bile canaliculi-like structures. 27 To date, this cell line has been used extensively as an ideal model to assess TGF-b-induced EMT on the resultant cellular phenotypes and gene expression profiles in vitro. 8,18,24 When exposed to TGF-b1 for 48 hours, AML12 cells underwent EMT, in which cells lost their epithelial honeycomb-like morphology and obtained a spindle-like shape ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis we used mouse AML12 cells, a normal cell line that exhibits typical hepatocyte features, such as peroxisomes and bile canaliculi-like structures. 27 To date, this cell line has been used extensively as an ideal model to assess TGF-b-induced EMT on the resultant cellular phenotypes and gene expression profiles in vitro. 8,18,24 When exposed to TGF-b1 for 48 hours, AML12 cells underwent EMT, in which cells lost their epithelial honeycomb-like morphology and obtained a spindle-like shape ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cells grow indefinitely but without anchorage-independent growth potential, such as colony formation in soft agar or tumor development in immune-deficient mice. 32 Using this cell line, we could determine whether mutant b-catenin is a transforming oncogene. We first established a cell line that stably expresses mutant b-catenin.…”
Section: Establishment and Characterization Of Aml12 B-catenin Stablementioning
confidence: 99%
“…31 It is critical to investigate the molecular pathways that are involved in the tumorigenesis, in order to design better treatment for this fatal disease. A murine hepatocyte cell line AML12, established by Wu et al from a human transforming growth factor a (TGFa) transgenic mouse, 32 has been used as a cell model to study the tumorigenic activity of hepatitis B viral pX protein. 33 In this study, the investigators demonstrated that the pX protein was capable of transforming the immortalized hepatocytes as determined by anchorage-independent cell growth assay.…”
mentioning
confidence: 99%
“…We employed hepatocytes obtained from mice transgenic for human TGF-␣ (hTGF-␣) (26,46). hTGF-␣-transformed hepatocytes (designated AML12 hepatocytes) are well differentiated and can be passaged for many times without loss of differentiation (46). Evidence has been accumulating that AML12 hepatocytes represent an adequate and reproducible model for long-term studies of hepatocyte proliferation, survival, and neoplastic transformation (5,40).…”
mentioning
confidence: 99%
“…We employed hepatocytes obtained from mice transgenic for human TGF-␣ (hTGF-␣) (26,46). hTGF-␣-transformed hepatocytes (designated AML12 hepatocytes) are well differentiated and can be passaged for many times without loss of differentiation (46).…”
mentioning
confidence: 99%